Validation of psychometric properties and development of response criteria for the psoriasis symptoms and signs diary (PSSD): results from a phase 3 clinical trial. (2nd January 2019) - Armstrong, April; Puig, Luis; Langley, Richard; Tsai, Tsen Fang; Song, Michael; Wasfi, Yasmine; Jiang, Jingzhi; Li, Shu; Han, Chenglong
Abstract: Purpose: The Psoriasis Symptoms and Signs Diary (PSSD) is a patient-reported instrument that assesses severity of six symptoms (itch, skin tightness, burning, stinging, and pain) and five signs (dryness, cracking, scaling, shedding/flaking, redness, and bleeding) of psoriasis. Materials and methods: PSSD symptoms and signs summary scores (range, 0–100) were derived based on individual item scores (0–10 [absent-worst imaginable]). Using Psoriasis Area and Severity Index [PASI], Investigator's Global Assessment [IGA] and Dermatology Life Quality Index [DLQI]) data from the NAVIGATE trial of patients with moderate-to-severe psoriasis, analyses were conducted to further validate the PSSD (7-day recall version) and establish criteria for clinically meaningful improvements (CMIs). Results: Mean PSSD symptoms and signs summary scores were 50.6 and 60.7, respectively, at baseline, with no major floor (score of 0) or ceiling (maximum score) effects. PSSD scores and changes in PSSD scores were highly correlated with PASI, IGA, and DLQI scores (most Spearman's correlation r 's ≥0.4, all p  < .001). A 2-grade improvement in IGA or an improvement of 75%-<90% in PASI was associated with CMIs of ≥40-points in PSSD summary scores and ≥3–5-points in individual item scores. Conclusions: The PSSD possesses strong psychometric properties and is suitable for use as a measure of disease severity in clinical studies of patients with moderate-to-severe psoriasis.